Paleoclimate, paleoweathering and paleoredox conditions of Lower Cretaceous shales from the Mural limestone, Tuape section, northern Sonora, Mexico: Constraints from clay mineralogy and geochemistry - Jayagopal Madhavaraju; Erik Ramírez-Montoya; Rogelio Monreal; Carlos M. González–León; Teresa Pi-Puig; Inocente G. Espinoza-Maldonado; Francisco J. Grijalva-Noriega (Revista Mexicana de Ciencias Geológicas)
Clay mineral analysis and major, trace and rare earth elements (REE) data were used in this study to interpret the paleoclimatic changes, paleoweathering and paleo-redox conditions in shale beds of the Tuape section of the Mural Limestone of Sonora. The clay mineralogical assemblages (illite-chlorite-kaolinite-smectite) of this section have provided information on the climatic conditions and environment of deposition that prevailed during late Aptian-early Albian age. The chondrite-normalized REE patterns are characterized by enriched LREE, flat HREE with negative Eu anomaly. The chemical index of alteration (CIA) and plagioclase index of alteration (PIA) values for these shales and A-CN-K diagram indicate a moderate intensity of chemical weathering. The low contents of TOC, TN, Mo, U and V and low Ni/Co and U/Th ratios in the Cerro La Ceja, Los Coyotes and Mesa Quemada members suggest that they have been deposited under oxic conditions. However, the Tuape Shale and Cerro La Puerta members show relatively low to moderate contents of redox sensitive elements, and their ratios suggest that the depositional basin experienced oxic to anoxic depositional conditions.